(untitled) (Texas Journal of Philology, Culture and History, 2026)
This article explores how the details of the earthquake that struck the Andijan region in the early 20th century were reflected in the poetry of Fergana Valley and Tashkent poets during the National Awakening period. It analyzes the lyrical works of Nuri, Khujakhon Khoja Roji Margilani, Karimbek Kami, and Iskhokkhon Ibrat, highlighting their shared ideological perspective on the causes and consequences of the disaster. The study examines how these poets depicted the psychological and physical suffering of the Andijan people, employing traditional poetic techniques to express deep sympathy for the victims. Additionally, it compares their mastery of traditional imagery, use of symbolic language, and the integration of realism in their poetic style, providing a comprehensive analysis of their artistic approach